Wandering along the Moebius strip: Radical reflexivity in the archaeology of educational research - Saari, Antti (Kultura-Społeczeństwo-Edukacja, 2019)
Writing qualitative research texts often involves the acknowledgement of the researcher being imbued in the systems of meaning that he or she is studying. This provides a background for incitement to reflexivity, i.e. how one’s own life history and broader cultural context is etched in epistemological and ontological assumptions about the object. This article studies the reflexive style of writing in Michel Foucault’s archaeology of the human sciences, which constantly problematises its own assumptions about studying discourses. His style is described with the analogy of a Moebius strip, highlighting the way the ‘outside’ history of the human sciences turns into the ‘inside’ conditions of possibility for analysing discursive formations in the history of educational research.